How co-locating public mental health interventions in community settings impacts mental health and health inequalities: a multi-site realist evaluation - Cleo Baskin; Fiona Duncan; Emma A. Adams; Emily J. Oliver; Gillian Samuel; Shamini Gnani (BMC Public Health, 2023)
Abstract Background Public mental health interventions are non-clinical services that aim to promote wellbeing and prevent mental ill health at the population level. In England, the health, social and community system is characterised by complex and fragmented inter-sectoral relationships. To overcome this, there has been an expansion in co-locating public mental health services within clinical settings, the focus of prior research. This study evaluates how co-location in community-based settings can support adult mental health and reduce health inequalities. Methods A qualitative multi-site case study design using a realist evaluation approach was employed. Data collection took place in three phases: theory gleaning, parallel testing and refining of theories, and theory consolidation. We collected data from service users (n = 32), service providers (n = 32), funders, commissioners, and policy makers (n = 11), and members of the public (n = 10). We conducted in-depth interviews (n = 65) and four focus group discussions (n = 20) at six case study sites across England, UK, and two online multi-stakeholder workshops (n = 20). Interview guides followed realist-informed open-ended questions, adapted for each phase. The realist analysis used an iterative, inductive, and deductive data analysis approach to identify the underlying mechanisms for how community co-location affects public mental health outcomes, who this works best for, and understand the contexts in which co-location operates. Results Five overarching co-location theories were elicited and supported. Co-located services: (1) improved provision of holistic and person-centred support; (2) reduced stigma by creating non-judgemental environments that were not associated with clinical or mental health services; (3) delivered services in psychologically safe environments by creating a culture of empathy, friendliness and trust where people felt they were being treated with dignity and respect; (4) helped to overcome barriers to accessibility by making service access less costly and more time efficient, and (5) enhance the sustainability of services through better pooling of resources. Conclusion Co-locating public mental health services within communities impacts multiple social determinants of poor mental health. It has a role in reducing mental health inequalities by helping those least likely to access services. Operating practices that engender inter-service trust and resource-sharing are likely to support sustainability.